2020
DOI: 10.1177/2158244020963131
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experiences of Females With Entrepreneurship in Sudan: Networking, Social Expectations, and Family Support

Abstract: Extensive research exists on female entrepreneurship in developed countries such as North America and Europe; however, there is limited research on women entrepreneurs in African nations, specifically in Sudan. This descriptive phenomenological research was designed to explore, discover, and describe the perceptions and lived experiences of successful Sudanese female entrepreneurs concerning overcoming the challenges and obstacles faced in the beginning and managing new businesses in the region of Khartoum, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
9
2
Order By: Relevance
“…In many countries around the world, women entrepreneurs have limited financial resources due to the substantial requirements of lenders (Aragon‐Sanchez et al, 2017). Said and Christine (2020) pointed out that many females may intend to become entrepreneurs, but accessing capital is what hinders them. Hence, they started small businesses that required a small amount of money.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In many countries around the world, women entrepreneurs have limited financial resources due to the substantial requirements of lenders (Aragon‐Sanchez et al, 2017). Said and Christine (2020) pointed out that many females may intend to become entrepreneurs, but accessing capital is what hinders them. Hence, they started small businesses that required a small amount of money.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…They are motivated to be hard‐working entrepreneurs when their families support them financially and emotionally. When a family is supportive, women feel encouraged and fearless to start a new business (Said & Christine, 2020). Osorio et al (2017) confirmed that a family is essential in individuals' intentions to start new ventures.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In patriarchal societies, mother-in-laws may pose normative barriers preventing women to take up entrepreneurship even when resources are available (Karim, 2022). The family support and motivation help women entrepreneurs to become successful (Said and Enslin, 2020). Research has documented women discouraging their children to take up entrepreneurship due to sociocultural practices (Akinbami, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, there is an urgent need for decision-makers in Sudan to know more about this important segment of society, the extent of its contribution to the national economy, and how to support it and protect its human and civil rights, especially during the COVID-19 pandemic so that all challenges can be overcome, and the problems facing the work of Sudanese businesswomen, which did not come as an opponent over the man, but for his participation to confront the economic conditions that have become burdensome for families and for integration and the formation of an addition to the Sudanese family. It appears that the major problem is the one that women workers in marginal professions face, whether in selling tea and food or domestic workers, especially since most of them are displaced from war and conflict areas and went to work for compelling reasons, including the absence of the breadwinner, until they face daily persecution by means of the authorities confiscate their tools, unfair trials with fines, and prosecute them with social stigma (Said & Enslin, 2020).…”
Section: The Scenario In Sudanmentioning
confidence: 99%